2020
DOI: 10.1097/md.0000000000023870
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities associated with different levels of total cholesterol in male and female acute ischemic stroke patients

Abstract: Men and women differ in their clinical risk factors with respect to various predictors of severity in acute ischemic stroke (AIS). High cholesterol is a risk factor for AIS and the mechanism by which high cholesterol levels lead to an AIS is well established. However, the specific relationship between demographic, clinical risk factors, total cholesterol, and the resulting gender difference in AIS patients is yet to be investigated. This study recruited AIS patients between January 2000 and June 2016 classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
2
8
0
1
Order By: Relevance
“…In previous studies, lower BP levels were associated with improved prognosis in patients treated with AIS, while higher BP levels were associated with poor treatment outcomes [ 28 , 29 ]. Our results extend beyond previous reports on elevated BP and stroke severity in the non-telestroke setting [ 22 , 23 , 30 , 31 ]. Most studies did not report specific risk factors associated with stroke severity in AIS patients with elevated DBP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In previous studies, lower BP levels were associated with improved prognosis in patients treated with AIS, while higher BP levels were associated with poor treatment outcomes [ 28 , 29 ]. Our results extend beyond previous reports on elevated BP and stroke severity in the non-telestroke setting [ 22 , 23 , 30 , 31 ]. Most studies did not report specific risk factors associated with stroke severity in AIS patients with elevated DBP.…”
Section: Discussionsupporting
confidence: 88%
“…Several risk factors, such as diabetes, hypertension, atrial fibrillation, coronary and peripheral artery disease, heart failure, and age, have been associated with stroke severity [ 22 , 23 , 24 ]. In addition, the severity conferred by the different risk factors often clusters among those with pre-existing hypertension and may significantly contribute to stroke severity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 32 33 ] Findings indicate that women were more likely to have a poor outcome than men. While hormonal factors and comorbid function are known to contribute to the poor functional recovery in older women, our study reveals that well-established factors including previous stroke,[ 34 35 ] AF,[ 36 ] heart failure,[ 37 ] antidepressant use,[ 38 ] higher blood glucose level,[ 39 ] higher heart rate,[ 40 ] and rtPA administration[ 41 ] are all linked to worsening outcome in the elderly patient population. After adjusting for the effect of confounding variables, our findings reveal that several clinical risk factors contribute to the continuous decline in neurologic outcome in older female AIS patients, which suggests that long-term management strategies are needed for older stroke populations.…”
Section: Discussionmentioning
confidence: 97%
“…Women are more likely to present with hypertension, diabetes mellitus, and obesity [ 12 , 35 ]. In contrast, men are more likely to present with a history of heart disease, myocardial infarction, peripheral arterial disease, current smoking, and alcohol consumption [ 5 , 6 , 36 , 37 ]. Our current study found that women presenting with AIS with increased heart rate treated in the telestroke network were associated with worsening neurologic functions.…”
Section: Discussionmentioning
confidence: 99%